ОСОБЛИВОСТІ РОЗВИТКУ ІНШОМОВНОЇ КОМУНІКАТИВНОЇ КОМПЕТЕНЦІЇ СТУДЕНТІВ ВИЩИХ НАВЧАЛЬНИХ ЗАКЛАДІВ (Педагогіка вищої та середньої школи, 2008)
The article deals with the research of communicative competence development peculiarities of the students of higher educational establishments. The paper describes 6 stages of training activity of the students based on the support materials as a means of educational and pedagogic purposes of training practice reaching.